THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND CORPORATE ETHICAL VALUES ON THE RELATIONSHIP BETWEEN VALUE CONGRUENCE WITH INNOVATIVE WORK BEHAVIOUR, ORGANIZATIONAL SOCIAL CAPITAL AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Nikhil Varghese (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Using theories of innovative work behaviour (IWB) and value congruence (VC) this study attempts to examine the effect of transformational leadership (TL) and corporate ethical values (CEV) on the relationship between value congruence with innovative work behaviour (IWB), organizational social capital (OSC) and organizational citizenship behaviour (OCB). Data were collected from 268 employees of a public sector power distribution company of a central Indian province in August-September (2019). Data reveals that transformational leadership and corporate ethical values both moderate the relationship between value congruence with IWB, OSC and OCB. Results also revealed that VC mediates between the relationship of TL and CEV with IWB, OSC and OCB.